Articulation Of Public Educational Policies with the Chilean School Curriculum - Pérez Carvajal, Alejandro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of the article is to analyze the implementation of public educational policies, Preferential School Subsidy and the Program of Accompaniment and Effective Access to Higher Education, in the context of the articulation with the National Curriculum Policy (PCN) in public settings, every time implemented, no evidence is observed about its articulation with PCN at the micro level. The study had a qualitative approach, in four schools of the Metropolitan Region. As a result, each case presents different levels of implementation, likewise there are no evidence of previous articulating mechanisms in the design of each policy at the micro level.